Bluetongue and epizootic haemorrhagic disease virus in local breeds of cattle in Kenya - Toye, Philip G.; Batten, C.A.; Kiara, Henry K.; Henstock, M.R.; Edwards, L.; Thumbi, Samuel M.; Poole, Elizabeth J.; Handel, Ian G.; Bronsvoort, B.M. de C.; Hanotte, Olivier H.; Coetzer, Jacobus A.W.; Woolhouse, Mark E.J.; et al. (Elsevier, 2013)
The presence of bluetongue virus (BTV) and Epizootic Haemorrhagic Disease virus (EHDV) in indigenous calves in western Kenya was investigated. Serum was analysed for BTV and EHDV antibodies. The population seroprevalences for BTV and EHDV for calves at 51 weeks of age were estimated to be 0.942 (95% CI 0.902–0.970) and 0.637 (95% CI 0.562–0.710), respectively, indicating high levels of circulating BTV and EHDV. The odds ratio of being positive for BTV if EHDV positive was estimated to be 2.57 (95% CI 1.37–4.76). When 99 calves were tested for BTV and EHDV RNA by real-time RT-PCR, 88.9% and 63.6% were positive, respectively. Comparison of the serology and real-time RT-PCR results revealed an unexpectedly large number of calves that were negative by serology but positive by real-time RT-PCR for EHDV. Eight samples positive for BTV RNA were serotyped using 24 serotype-specific real-time RT-PCR assays. Nine BTV serotypes were detected, indicating that the cattle were infected with a heterogeneous population of BTVs. The results show that BTV and EHDV are highly prevalent, with cattle being infected from an early age.